ADAPTING MEG CABOT’S PRINCES DIARIES IN TEACHING WRITING - Pramugara Robby Yana; Zahara Ramadani (Bandar Lampung University (UBL), 2016)
This article is written to describe the use of literary work particularly novel entitled Princess Diaries written by Meg Cabot in teaching writing. Writing is a very eminent skill in English language teaching and learning. It is a skill that helps students to put their thoughts into words in a meaningful form and to interact with the message mentally. However, among the four skills in English language and teaching, writing is claimed as the hardest one to be improved. Therefore, the use of literary work is believed to make students improve their writing ability. Adapting Meg Cabot’s Princess Diaries in teaching writing has many advantages including (1) expanding students’ awareness of language usage of the foreign language, (2)providing cultural enrichment , (3) engaging students’ interest that boost their motivation to learn, (4) developing students’ interpretative abilities, (5) the students could get better ideas to write, (6) the students could get better understanding about several basic techniques of writing, and (7) the teaching and learning process become more effective. The first step in adapting Meg Cabot’s Princess Diaries in teaching writing is introducing what teen-lit is to the students. Then, the students are asked what probably the novel is about based on the title. After that, the students read some parts in the beginning of the teen-lit to get to know the characters and the plot of the story. In order to deal with limited time provided in the classroom, students are asked to read the other chapters at home or each student need to read certain chapters before discuss it together in the next meeting. The final goal is that students are able write a review of the novel or to write a recount text based on the journal form of the novel.